A grounded theory model for reducing stigma in health professionals in Canada. (August 2016) - Knaak, S.; Patten, S.
Abstract : Objective: The Mental Health Commission of Canada was formed as a national catalyst for improving the mental health system. One of its initiatives is Opening Minds (OM), whose mandate is to reduce mental health‐related stigma. This article reports findings from a qualitative study on antistigma interventions for healthcare providers, which includes a process model articulating key stages and strategies for implementing successful antistigma programmes. Method: The study employed a grounded theory methodology. Data collection involved in‐depth interviews with programme stakeholders, direct observation of programmes, a review of programme documents, and qualitative feedback from programme participants. Analysis proceeded via the constant comparison method. A model was generated to visually present key findings. Results: Twenty‐three in‐depth interviews were conducted representing 18 different programmes. Eight programmes were observed directly, 48 programme documents were reviewed, and data from 1812 programme participants were reviewed. The analysis led to a four‐stage process model for implementing successful antistigma programmes targeting healthcare providers, informed by the basic social process 'targeting the roots of healthcare provider stigma'. Conclusion: The process model developed through this research may function as a tool to help guide the development and implementation of antistigma programmes in healthcare contexts.